2022
DOI: 10.47814/ijssrr.v6i11.617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Current Ratio, Return on Assets and Debt to Equity Ratio on Profit Growth in Listed Banking Companies on the Indonesia Stock Exchange Year 2019-2021

Abstract: This study aims to determine and analyze the effect of Current Ratio, Return On Assets, and Debt to Equity Ratio To Profit Growth on Banking Companies Listed on the Indonesia Stock Exchange in 2019-2021. The population in this study was 43 registered banking companies on the Indonesia Stock Exchange for the 2019-2021 period using the purposive method sampling obtained 18 companies that met the criteria. Test methods that multiple linear regression analysis is used. The results show that the Current Ratio, Retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
3
1
0
1
Order By: Relevance
“…A rise in the Return on Assets (ROA) value is expected to enhance the efficiency of the Village Credit Institution Badung Regency in utilizing VCI assets, hence potentially leading to an increase in Profit Growth. The findings of this study are consistent with the findings of Paramithari and Sujana (2022), Bimantoro and Ardiansah (2018), Dewi and Puspaningsih (2020), Mislinawati and Sari (2020), Hidayati and Marlina (2021), Ester et al (2022), Karelina et al (2022), Siswanto et al (2022), and Karim et al (2023. In essence, the findings of this study can serve as a foundation for the office manager of VCI to strategically utilize resources.…”
Section: Source: Processed Data Figure 1 Results Of Normality Testsupporting
confidence: 92%
See 3 more Smart Citations
“…A rise in the Return on Assets (ROA) value is expected to enhance the efficiency of the Village Credit Institution Badung Regency in utilizing VCI assets, hence potentially leading to an increase in Profit Growth. The findings of this study are consistent with the findings of Paramithari and Sujana (2022), Bimantoro and Ardiansah (2018), Dewi and Puspaningsih (2020), Mislinawati and Sari (2020), Hidayati and Marlina (2021), Ester et al (2022), Karelina et al (2022), Siswanto et al (2022), and Karim et al (2023. In essence, the findings of this study can serve as a foundation for the office manager of VCI to strategically utilize resources.…”
Section: Source: Processed Data Figure 1 Results Of Normality Testsupporting
confidence: 92%
“…Previous studies have demonstrated a positive and significant relationship between Return on Assets and profit growth. This finding aligns with the findings of Karim et al (2023), Paramithari and Sujana (2016), Bimantoro and Ardiansah (2018), Dewi and Puspaningsih (2020), Mislinawati and Sari (2020), Karelina et al (2022), Hidayati and Marlina (2021), Ester et al (2022) and Siswanto et al (2022). Based on the above explanation, the aforementioned statement can be considered a hypothesis: H4: PG is positively influenced by ROA…”
Section: Effect Of Return On Assets (Roa) On Profit Growthsupporting
confidence: 89%
See 2 more Smart Citations
“…Hasil ini menujukkan bahwa peningkatan struktur mendukung peningkatan pertumbuhan aset, namun masih belum signifikan karena perusahaan property merupakan industri yang pergerakannya cepat merespon kondisi ekonomi yang terjadi, sehingga saat kondisi ekonomi memburuk akan membuat performa emiten perusahaan properti juga menurun dengan cepat. Anggapan bahwa struktur modal memiliki dampak yang positif pada pertumbuhan aset sejalan dengan penelitian (Karelina et al 2022). Hasil analisis yang telah dilakukan pada profitabilitas merupakan variabel yang memberikan dampak paling besar bagi pertumbuhan asset perusahaan.…”
Section: Metode Penelitianunclassified